Analysis of the Institutional Capacity as a Part of the Institutional Economics: Evidence from the Organizational Capacity of Surakarta City Local Government - Riyardi, Agung; Widojono, W; Isa, Muzakar (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2015)
The institutional capacity is a part of the institutional economics. There are two standards of the institutional capacity. The first standard is the optimality capacity of micro, mezzo, and macro levels. The second standard is the criteria of expertise, specificity, and incentives. However, analysis on the concept of institutional capacity is limited. Therefore, this study aimed to analyze the application of the institutional capacity in Surakarta city local government and to obtain empirical facts of the optimal capacity of micro, mezzo and macro levels and its correlation with the institutional criteria. Descriptive method was applied to measure the capacity optimization in the micro, mezzo, and macro levels and to describe its correlation with the institutional criteria, namely expertise, specificity, and incentives. To examine the level of the capacity optimization, the percentage of the expected and prevailed was analyzed, whereas the dynamics of each criterion since 2005 to 2011 was analyzed to illustrate the correlation with the institutional criteria. The study indicated the overall capacity of Surakarta city government has not been optimal, due to their suboptimal mezzo and macro levels capacity. In addition, the capacity of micro, mezzo and macro level of Surakarta government turns to have correlation with the institutional criteria. The micro level correlates with the expertisecriterion, the mezzo level with the specificity in authority and incentives criteria, andthe macro level with the specificity in responsiveness criteria.